2015
DOI: 10.1016/j.jpeds.2015.04.076
|View full text |Cite
|
Sign up to set email alerts
|

Racial/Ethnic Differences in Pediatric Brain Tumor Diagnoses in Patients with Neurofibromatosis Type 1

Abstract: Objective To evaluate evidence for differences in pediatric brain tumor diagnoses by race and ethnicity using a cross-sectional study design in individuals with neurofibromatosis type 1 (NF1). Study design Subjects with NF1 were ascertained from the NF1 Patient Registry Initiative (NPRI) and through a clinical record database of patients at a large academic medical center. Logistic regression was employed to calculate odds ratios (ORs) and 95% confidence intervals (CIs) to analyze differences in the odds of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 34 publications
1
13
0
1
Order By: Relevance
“…Glioma risk factors, and specifically OPGs, in NF1 are not well-defined. A number of studies have reported that individuals with European ancestry are more likely to be diagnosed with an OPG than those with other ancestries [510]. In addition, the results of two small studies suggest that children with NF1 gene mutations occurring toward the 5′ end are more likely to develop an OPG [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Glioma risk factors, and specifically OPGs, in NF1 are not well-defined. A number of studies have reported that individuals with European ancestry are more likely to be diagnosed with an OPG than those with other ancestries [510]. In addition, the results of two small studies suggest that children with NF1 gene mutations occurring toward the 5′ end are more likely to develop an OPG [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Of note, our previous studies suggest that NF1 [23] and PBT diagnoses are reported with good accuracy for NPRI participants [13]. For allergic condition diagnoses, participant/parent legal guardian reported data could result in misclassification of subjects with respect to allergic condition diagnoses if conditions are not actually present in the participant or they are present and not reported.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to informing the underlying biology of PBTs, identification of factors that modulate risk is a critical component of developing PBT risk prediction models for this population and for developing prevention strategies. To date, some studies have indicated that individuals with African ancestry are at lower risk of PBT development than those with European ancestry [813] and two small studies have suggested that children harboring NF1 gene mutations closer to its 5′ end are more likely to develop OPGs [14, 15]. …”
Section: Introductionmentioning
confidence: 99%
“…While there is evidence for differences in racial and ethnic group risks for brain tumors [63], the most compelling data to support the existence of modifier loci derives from Nf1 genetically-engineered mouse models [64]. In these studies, NPcis mice, which carry mutations in the Nf1 and Trp53 genes on the same chromosome, develop HGG.…”
Section: Genomic/genetic Levelmentioning
confidence: 99%